Asuhan Keperawatan Keluarga TN. ST Dengan Gangguan Sistem Muskuluskeletal : Rheumatoid Arthritis Pada TN. SD Di Desa Kutayu Dukuh Krajen RT 05 RW 02 Kecamatan Tonjong Kabupaten Brebes - Dian Fitriana; Esti Nur Janah; Siti Fatimah (STIKes Ibnu Sina Ajibarang, 2023)
Rheumatoid arthritis or what is often called rheumatism is a disease caused by chronic systemic inflammation. This disease attacks flexible joints and can affect the work or structure of the tissues and organs of the human body around the joints (Purba, Marlina, & Arianto, 2020). This disease is included in the autoimmune disease group which mostly attacks the elderly (Fatmawati & Ariyanto, 2020).